Behavior Facing Hoaxes among Housewives - Ali Kusumadinata; Alisa Adelia; Feni Trihidayani; Dewi Rahayu Islmaniati; Helwa Nur Alfa Laila; Ivan Maulana Yusuf; M. Maulana Rizik Sihabudin; Nurlatifah Khaerani; Raden Kharis Djoyo Seputro; Radja Raiyan Trixy Salafy (PT FORMOSA CENDEKIA GLOBAL, 2023)
Hoaxes are an integral part of free communication today, especially in every field. Hoaxes have an impact on society and harm society, therefore they contain legal consequences. Housewives are objects that have a major impact on hoax information. So this study aims to see how the behavior of dealing with hoaxes experienced by housewives can be prevented by them. The research method is carried out with qualitative techniques by building a verstehen conception that occurs in every moment that learning can take. The analysis is done by building a story construction and drawing in a generalization of the discussion. The results of this study show that housewives have strong resistance to the support of institutions that protect the construction opinion information generated. This is supported by the support of the recitation community, community leaders, religion, and customs as well as household leaders.